Study on the Formation Mechanism of Shale Roof, Floor Sealing, and Shale Self-Sealing: A Case of Member I of the Upper Ordovician Wufeng Formation–Lower Silurian Longmaxi Formation in the Yangtze Region - Zhang, Ziya; Zhang, Kun; Song, Yan; Jiang, Zhenxue; Jiang, Shu; Wang, Pengfei; Li, Yong; Yin, Xiangdong; Chen, Zhiyuan; Li, Zhengwei; Yuan, Xuejiao; Liu, Pei; et al. (Frontiers in Earth Science, 2021)
Similar to North America, China has abundant shale resources. Significant progress has been made in the exploration and exploitation of shale gas in China since 2009. As the geological theory of unconventional oil and gas was proposed, scientists have started researching conditions for shale gas preservation. The shale roof and floor sealing and the shale self-sealing are the critical objects of such research, which, however, are still in the initial stage. This paper studied the formation mechanism of shale roof and floor sealing and shale self-sealing by taking the marine shales from Member I of the Upper-Ordovician Wufeng Formation–Lower Longmaxi Formation in the Upper Yangtze Region as the research object. We performed analyses on the TOC content, mineral composition, and porosity, as well as the FIB-SEM, FIB-HIM and gas permeability experiments on the core samples collected from the marine shales mentioned above. The conclusions are as follows: for the sealings of shale roof and floor, the regional cap rocks, roof, and floor provide sealing for shales due to physical property differences. For the self-sealing of shales, the second and third sub-members of Member I of the Wufeng Formation-Longmaxi Formation mainly develop clay mineral pores which are dominated by macropores with poor connectivity, while the first sub-member of Member I of the Wufeng Formation – Longmaxi Formation mainly develops organic-matter pores, which are dominated by micropores and mesopores with good connectivity. Due to the connectivity difference, the second and third sub-members provide sealing for the first sub-member, while the methane adsorption effect of shales can inhibit large-scale shale gas migration as it decreases the gas permeability; thus, the organic-rich shales from the first sub-member of Member I of the Wufeng Formation – Longmaxi Formation provides sealing for itself.